(STUDY ON) THE EFFECT OF VARIETIES AND TYPE SOAKING SOLUTIONS ON THE QUALITY OF POWDERED SHALLOTS - Ericha Nurvia Alami; Erni Sofia Murtini; Sudarminto Setyo Yuwono (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
Powdered shallots have a broad market potential to be developed to meet the trend of modern lifestyles. The suitability of raw material varieties and the type of soaking solutions are necessary to produce good quality shallot powder. This study aims to examine the types of varieties and soaking solutions on the quality of powdered shallots based on the organoleptic test. This study used a Randomized Block Design (RBD) of 2 factors, namely the shallots variety factor (biru lancor, super philip, rubaru) and the type of soaking solution (salt, ascorbic acid, citric acid). Repetition was carried out three times for each treatment unit so that 27 experimental units were obtained. Observation parameters include yield, water activity (Aw value), colour, hygroscopicity, moisture content, and organoleptic test, followed by determining the best treatment using a comparison method between Zeleny and SMART. The results showed that best-powdered shallots were derived from the biru lancor varieties with the citric acid soaking solution. The panelists gave scores of 8.00 (like very much) for the colour, 6.83 (like moderately) for the aroma and 6.30 (like slightly) for the flavor of the powdered shallots. These powdered shallots have water content value of 3.17%, the yield of 6.81%, hygroscopicity level of 3.12%, Aw 0.39, colour L* 73.53, a* 11.73, b * 4.87.